A systematic review of technology-infused physical activity interventions in K-12 school settings: effectiveness, roles, and implementation strategies - Taemin Ha; Jongho Moon; Hyeonho Yu; Xiaoping Fan; Lisa Paulson (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Rapid technological advancements have rendered many prior reviews of technology-integrated physical activity (PA) interventions in K–12 schools obsolete. A comprehensive analysis examining both the effects of these interventions and the specific roles that technology plays has been notably lacking. This review aimed to systematically examine the effects of technology-infused PA interventions and identify the specific types, roles, and contextual applications of technology within K–12 schools. Methods This systematic review adhered to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. A thorough search across seven electronic databases (CINAHL, ERIC/EBSCOhost, PsycINFO, PubMed/MEDLINE, Scopus, SPORTDiscus, and Web of Science) included studies published up to May 20, 2024. Only randomized controlled trials (RCTs), cluster-RCTs, or rigorous quasi-experimental designs with matched/statistically controlled comparisons (N-RCTs) examining technology-infused PA interventions for school-aged children and adolescents were considered. Results Fifty-eight studies met inclusion criteria. Wearable devices (e.g., accelerometers) were the most used for PA measurement. Other technologies like web-based platforms, mobile applications, and exergaming served as educational tools, communication platforms, or core intervention components. Interventions occurred primarily in classrooms, followed by physical education spaces, and extended to home/online environments, school breaks (e.g., recess), and before-school time. Overall, interventions positively affected PA levels and related outcomes (e.g., PA enjoyment), though effectiveness varied by technology type, design, and context. Conclusions Technology holds substantial potential to enhance PA promotion in schools, but its effectiveness hinges on well-designed interventions that consider the specific types and applications of technology.